2020
DOI: 10.3390/su12051748
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Action Gap by Democratizing Climate Change Education—The Case of k.i.d.Z.21 in the Context of Fridays for Future

Abstract: Formal schooling frequently lacks both democratic learning culture and effective climate change education (CCE). This study analyzes the effects of the participatory CCE initiative k.i.d.Z.21 and the impacts of the current Fridays For Future (FFF) climate protests on teenagers’ climate change awareness. The mixed-methods approach comprises online pre-and post-tests, and personal interviews with selected students. k.i.d.Z.21 follows moderate constructivist, inquiry-based learning approaches and addresses 14-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 70 publications
(109 reference statements)
1
29
0
2
Order By: Relevance
“…Protest is considered an important tool for drawing attention to issues and achieving political change (UNICEF 2020) and the recent world-wide climate "school strikes" provided dramatic evidence of children's ability to mobilise at scale. These strikes raised global public awareness of the climate change emergency (Thackeray et al, 2020) 1 and an Australian study of 14-year olds suggests such protest can complement education in terms of increasing climate change awareness and climate-friendly behaviour (Deisenrieder et al 2020). A surprisingly small minority (6.4%) of teachers in our sample considered that campaigning that might include legal demonstration should never appear in the school curriculum.…”
Section: Discussionmentioning
confidence: 81%
“…Protest is considered an important tool for drawing attention to issues and achieving political change (UNICEF 2020) and the recent world-wide climate "school strikes" provided dramatic evidence of children's ability to mobilise at scale. These strikes raised global public awareness of the climate change emergency (Thackeray et al, 2020) 1 and an Australian study of 14-year olds suggests such protest can complement education in terms of increasing climate change awareness and climate-friendly behaviour (Deisenrieder et al 2020). A surprisingly small minority (6.4%) of teachers in our sample considered that campaigning that might include legal demonstration should never appear in the school curriculum.…”
Section: Discussionmentioning
confidence: 81%
“…One study has shown that FFF is composed of very young people, mostly female (Wahlström et al, 2019), and another recently revealed that FFF is contributing to climate change awareness (Deisenrieder et al, 2020). FridaysForFuture has spread through both the embodied and the virtual dimensions.…”
Section: Fridaysforfuture: An Enactive Network?mentioning
confidence: 99%
“…Second, all layers of the systems appear to be interconnected both in reality and virtually. This increases knowledge transmission and improves the coordination of action but also boosts participation and engagement (Deisenrieder et al, 2020). In addition to its internal structure, FFF has developed an external network that extends into other fields such as science and economy but also draws in schools and parents.…”
Section: Nested Emergent Networkmentioning
confidence: 99%
See 2 more Smart Citations